2005
DOI: 10.1038/sj.ijo.0803138
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the adiponectin gene influences adiponectin expression levels in visceral fat in obese subjects

Abstract: Objective: Reduced serum adiponectin levels have been found in obesity and type 2 diabetes and variations in the adiponectin gene (APM1) have been associated with type 2 diabetes and features of the metabolic syndrome in different populations. Study Design: Here, we investigated the expression of APM1 in adipose tissue and studied the relationship between variation in APM1 expression, the APM1 G276T polymorphism, the common PPARG Pro12Ala polymorphism and clinical features of 36 morbidly obese (body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 52 publications
3
24
0
2
Order By: Relevance
“…Opposing also to our findings, other studies have provided that the 276 T allele was found to be protective for IR and the G/G genotype of SNP276 is a putative risk genotype which associated with lower plasma adiponectin levels and higher IR [30,31]. These conflicting association results in various populations suggesting a complex relationship between adiponectin gene variation and IR.…”
Section: Discussionsupporting
confidence: 59%
“…Opposing also to our findings, other studies have provided that the 276 T allele was found to be protective for IR and the G/G genotype of SNP276 is a putative risk genotype which associated with lower plasma adiponectin levels and higher IR [30,31]. These conflicting association results in various populations suggesting a complex relationship between adiponectin gene variation and IR.…”
Section: Discussionsupporting
confidence: 59%
“…This tendency was statistically significant in men showing that TT subjects had higher 3-year body weight gain. It was found that T-allele of the +276G/T polymorphism was associated with higher body fat in Swedish population [39] and with severe obesity in a French Caucasian population [40].…”
Section: Discussionmentioning
confidence: 99%
“…50 One of the latter, the T276G genotype, is characterized by markedly lower visceral adipose expression of adiponectin. 51 A second single nucleotide polymorphism, T45G, has been investigated in relation to PCOS, and studies have shown a statistically definable Adipokines in reproduction DB Campos et al correlation between the occurrence of this gene form and the ovarian disorder. 52,53 Recent findings indicate that adiponectin may also be active in the uterus and placenta.…”
Section: Effects Of Adiponectin On Reproduction and Fertilitymentioning
confidence: 99%